Analysis of Factors Affecting Indonesia's Crude Palm Oil (CPO) Export Volume to China (1990-2023) - Inayah Salwa, Adinda; Suandi, suandi; Effran, Endy (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This study aims to describe the characteristics of the development of Indonesia's CPO export volume to China, Indonesia's CPO production, CPO exports, exchange rates, Indonesia's inflation, and output from 1990-2023. This study uses secondary data obtained from UN Comtrade with HS Code 151110, the World Bank, the Central Bureau of Statistics and other sources related to this study. Data processing was carried out using multiple linear regression analysis tools with the ECM (Error Correction Model) method using Eviews Version 12 software. Statistical testing in this study used short-term estimates. The results of the study show that the development of Indonesia's CPO export volume to China, Indonesia's CPO production, CPO export prices, exchange rates, China's GDP, and Indonesia's inflation fluctuate every year.